Cellular infiltration, cytokines, and histopathology of skin lesions associated with different clinical forms and stages of naturally occurring lumpy skin disease in cattle. (November 2022) - Badr, Yassien; Noreldin, Ahmed E.; Elewa, Yaser Hosny Ali; Ahmed, Mohamed S.; Inoshima, Yasuo; Baker, Nabil M.; Aamer, Waleed Nabih; Abas, Osama M.; Nayel, Mohamed; Rahman, Md. Matiur; Elgendy, Emad; Saleh, Asmaa G.; et al.
Abstract: Lumpy skin disease (LSD) caused by the Capripoxvirus LSD virus which infects cattle, leading to a serious disease characterized by fever and the eruption of skin nodules all over the surface of the body. Our understanding of the pathogenesis of this disease is still incomplete, particularly the immunopathological alterations occurring in the skin nodules of infected animals. Therefore, we collected skin nodules from naturally infected cattle with different forms of the disease, both in the early stage of clinical infection and after disease progression. The skin samples were examined both histopathologically and immunohistochemically using a variety of antibodies targeting immune cellular markers and cytokines. As a result, the dermatohistopathology revealed orthokeratotic hyperkeratosis, vasculitis, epidermal microvesicles, and cellules claveleuses of Borrel in the early stage of infection, with the severity of the lesions correlating with the severity of the clinical disease. Meanwhile, late-stage samples had epidermal hyperkeratosis as well as dermal lymphocytic and histiocytic infiltrations. The predominant cellular infiltrates in the cutaneous lesions of early-stage LSD samples were interferon (IFN)-γ + cells and CD4 + T lymphocytes with few macrophage lineage cells. However, in the late-stage samples, numerous Iba-1 + macrophages, with few IFN-γ + cells and CD4 + T lymphocytes, were detected. Our findings indicate that IFN-γ + cells, CD4 + T lymphocytes, and macrophages play a key role in the immunity against natural LSD virus infection and imply that cutaneous vasculopathy associated with LSD virus infection is an immune-mediated lesion. The current study contributes to our understanding of the pathogenesis of LSD. Highlights: Interferon (IFN) + cells and CD4 + T lymphocytes are the predominant cellular infiltrates in early-stage lumpy skin disease (LSD) skin lesions. Iba-1 + macrophages infiltrates dominated in late-stage LSD skin lesions. Vasculopathy caused by LSD virus infection is most likely an immune-mediated lesion.